Autobiography of cotton : a novel - Rivera Garza, Cristina, 1964- (Graywolf Press, 2026)
"In 1934, a young Jose Revueltas traveled to Tamaulipas to support the cotton workers' strike in Estacion Camaron, which became the basis of his landmark novel Human Mourning. In her own groundbreaking novel, Autobiography of Cotton, Cristina Rivera Garza recounts her grandparents' journey from mining towns to those same cotton fields as it intersects with Revueltas's life in a vivid and evocative history of cotton cultivation along the Mexico-US border. Through archival research and personal narrative, Rivera Garza chronicles the way cotton transformed the borderlands by reconstructing the cotton workers' strike and reveals how cycles of deprivation and ecocide persist across generations. Deeply personal and politically acute, Rivera Garza crafts a new kind of border novel that tells how a brittle land radically altered her grandparents' lives and the territories they helped develop. An intimate fictionalization, Autobiography of Cotton reveals a rich social history of agricultural colonization, labor activism, environmental degradation, and cross-border migration"-- Provided by publisher.